The transition to reproductive senescence is characterized by increase in A6 and AVPV neuron activity with attenuation of noradrenaline content - Nicola, Angela Cristina [UNESP] (2016)
During the course of life, cyclic females face a state of midlife transition that occurs in a fully functioning neurological system, and results in reproductive senescence. The authors' hypothesis was that changes in the activity noradrenergic neurons may be one of the factors involved in this phenomenon. The aim of this study was to investigate the activity of the neurons in the anteroventral periventricular nucleus (AVPV) and locus coeruleus (LC), to analyze their role in determining reproductive senescence. Adult female Wistar rats in the diestrus phase (4 months/cyclic) and old females (18-20 months/acyclic) in persistent diestrus, were decapitated or perfused at three different time intervals (10, 14 and 18 h) throughout the day. In acyclic rats, the gonadotropin-releasing hormone (GnRH) and noradrenaline (NE) content were reduced; Fos-related antigen (FRA) in AVPV and Fos-related antigen/Tyrosine hydroxylase (FRA/TH) in LC showed immunolabeling of a higher number of neurons in these animals. The 3-methoxy-4-hydroxyphenylglycol/noradrenaline (MHPG/NE) ratio was higher and plasma LH was lower in the acyclic rats. Furthermore, the estradiol level was higher, and the progesterone level was lower after 14 h of persistent diestrus. These findings suggested that during the periestropause, there was a higher level of POA/AVPV and NE neuronal activity in the LC of acyclic rats, associated with a lower capacity of synthesis and storage of neurotransmitters and neurohormones contributed to changes in the temporal pattern of neuroendocrine signaling, thereby compromising the accuracy of inhibitory and stimulatory effects, causing irregularity in the estrous cycle and determining reproductive senescence.